Field lab Sme competitiveness - internationalization strategy: Egg electronics - in-depth analysis United States of America - Pina, Rodrigo Macedo De (2020)
This In-Depth Analysis was conducted as part of a Work Project. The goalw as to a ccurately analyze United States of America, as a potential country to internationalize to. Four dimensions were studied during this analysis– the quality of contacts in the country, the market sales potential, the competitive environment and the market entry conditions. For two ofthese dimensions ,a framework was created to, furtherin this Work Project, decide comparative lywhich of the analyzed countries was more suitable for EGG Electronics.